The Personality of Teachers in Islamic Education: A Study of the Qur'an Surah Ali 'Imran, Verse 159 - Uri, Fatimah; Anwar, Abu (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
The purpose of this research is to find out the personality of the teacher based on the interpretation of Surah Ali Imran verse 159. This study uses a literature review method with a descriptive qualitative approach, where data is collected through literature studies from primary and secondary sources related to the interpretation and concept of teacher personality. Data analysis is carried out by describing and interpreting the meaning of the verse as well as the views expressed in Tafsir Al-Azhar. The results of the study show that Surah Ali Imran verse 159 provides an overview of the personality of teachers who are full of gentleness, wisdom, and are able to lead with compassion, while prioritizing humility and deliberation in the learning process. These findings can be an important foundation for the development of teachers' character and professional ethics in the context of education.